PUBLIC EXPENDITURE MANAGEMENT IN PUNJAB AND KERALA: A COMPARATIVE STUDY - DEPTH ANALYSIS - Duhan, Pardeep Kumar; Vinati, (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper presents a comparative analysis of public expenditure management in Punjab and Kerala, two Indian states with distinct socio-economic backgrounds and governance frameworks. Both states have made significant strides in development, yet they face unique challenges related to public finance and expenditure efficiency. The research aims to evaluate the effectiveness of public spending in areas such as education, health, infrastructure, and welfare programs, assessing how fiscal policies and governance structures impact socio-economic outcomes in both regions. Using a mixed-method approach, the study examines quantitative data on public expenditure trends from the past decade, alongside qualitative insights gathered from interviews with policymakers and stakeholders. The findings reveal that while Kerala exhibits a higher level of expenditure efficiency, particularly in social sectors, Punjab struggles with fiscal deficits and underutilization of allocated funds. The analysis highlights the roles of institutional capacity, political will, and accountability mechanisms in shaping the effectiveness of public expenditure. Moreover, the study identifies best practices exemplified by Kerala's participatory budgeting and strong emphasis on transparency, which contribute to improved governance and citizen satisfaction. In contrast, Punjab's centralized decision-making process and insufficient public engagement are pointed out as key limitations in its expenditure management. The paper concludes with recommendations for enhancing public expenditure management in Punjab, emphasizing the need for decentralized governance, improved fiscal discipline, and greater accountability. The comparative insights drawn from Kerala's successful strategies provide valuable lessons that Punjab could adopt to achieve more effective public spending and foster sustainable development. This analysis contributes to the broader discourse on fiscal management in Indian states, offering a nuanced understanding of the dynamic interplay between governance, public expenditure, and socio-economic outcomes.